2012
DOI: 10.25035/ijare.06.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Can You swim? An Exploration of Measuring Real and Perceived Water Competency

Abstract: Little is known about the relationship between real and perceived water competence among youth in the context of drowning prevention or of their perceptions of their risk of drowning. This study reports the findings of an international project entitled Can You Swim? Collegiate physical education students (n = 373) were assessed in a two-part study using an initial questionnaire survey to provide self-estimates of water competency and risk perception, followed by six practical tests in the water. Correlation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 15 publications
2
54
2
3
Order By: Relevance
“…This is comparable, or even better, than adult sport science students in the "Can You Swim Study" where 33% could stay afloat for only 2 min. Additionally, 20% could stay afloat for only 2-6 min (Moran et al, 2012). The floating performance was found to be shorter in the unsteady condition compared with the calm water condition with respect to both performance rating score and floating time.…”
Section: Floating Time Decrements and Transfer Across Conditionsmentioning
confidence: 87%
See 1 more Smart Citation
“…This is comparable, or even better, than adult sport science students in the "Can You Swim Study" where 33% could stay afloat for only 2 min. Additionally, 20% could stay afloat for only 2-6 min (Moran et al, 2012). The floating performance was found to be shorter in the unsteady condition compared with the calm water condition with respect to both performance rating score and floating time.…”
Section: Floating Time Decrements and Transfer Across Conditionsmentioning
confidence: 87%
“…where several investigations were undertaken to reveal how well children transfer their skills from calm water conditions to unsteady or wavy water conditions and how perceived and real skills are performed in simulated unsteady, wavy, or choppy water conditions. It is part of a series of studies in the "Can You Swim" project (Moran et al 2012). A paired, randomized, repeated measures (test-retest) experimental design was chosen where the participants served as their own controls.…”
Section: Methods Participantsmentioning
confidence: 99%
“…(Moran et al, 2012). In this study, participants were asked to estimate their capacity to perform a range of skills deemed relevant to drowning prevention and then compare these estimates with practical assessment of the skills.…”
mentioning
confidence: 99%
“…Previous studies have shown that men are more likely to engage in risk-taking behavior once on the water and are also more likely to be under the influence of alcohol than women (Howland, Hingson, Mangione, Bell, & Bak, 1996;Lapa, Turgut, & Turgut, 2012). Further, men are more likely to overestimate their swimming skill and underestimate drowning risk (McCool, Moran, Ameratunga, & Robinson, 2008;Moran et al, 2012). Less well known, however, is our finding that males from rural areas drown at significantly higher rates than age-matched males living in non-rural areas.…”
mentioning
confidence: 58%